2021
DOI: 10.4314/ahs.v21i1.6s
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of antiretroviral therapy interruptions and factors influencing return to care at the Nkolndongo Health District, Cameroon

Abstract: Background: Antiretroviral therapy is a lifelong commitment that requires consistent intake of tablets to optimize health outcomes, attain and maintain viral suppression. Objective: We aimed to elicit predictors of treatment interruption amongst PLHIV and identify motivating factors influ- encing return to care. Method: We conducted a cross-sectional study using a mixed-method approach in four hospitals in Yaoundé. Sociodemo- graphic and clinical data were collected from ART registers. Using purposeful samplin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Among the 21 studies, three were conference abstracts [ 12 , 13 , 14 ] and the remainder were full papers (Table 1 ). Six studies were about general adult populations [ 12 , 14 , 15 , 16 , 17 , 18 ], nine were about women who started ART while pregnant [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ] and six were about various smaller populations (people who use drugs [ 13 ], indigenous people in an isolated area [ 28 ], adolescents [ 29 ], gay/bisexual/other men who have sex with men [ 30 ], men only [ 31 ] and women only [ 32 ]). No studies included children.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the 21 studies, three were conference abstracts [ 12 , 13 , 14 ] and the remainder were full papers (Table 1 ). Six studies were about general adult populations [ 12 , 14 , 15 , 16 , 17 , 18 ], nine were about women who started ART while pregnant [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ] and six were about various smaller populations (people who use drugs [ 13 ], indigenous people in an isolated area [ 28 ], adolescents [ 29 ], gay/bisexual/other men who have sex with men [ 30 ], men only [ 31 ] and women only [ 32 ]). No studies included children.…”
Section: Resultsmentioning
confidence: 99%
“…The number of included disengaged participants per study ranged from 6 to 5008 people. Nine studies had quantitative surveys [ 12 , 13 , 15 , 16 , 19 , 20 , 21 , 32 , 33 ] (including studies where this was done alongside in‐depth interviews) and 14 studies included at least some information about how frequently various reasons were reported by participants [ 12 , 13 , 14 , 15 , 16 , 17 , 19 , 20 , 21 , 22 , 23 , 24 , 31 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Thirty studies [ 18 , 31 59 ] reported barriers to ART adherence and 11 of the studies [ 31 34 , 37 , 39 , 43 , 46 , 53 , 55 , 56 ] also reported facilitators to ART adherence. Both the barriers and facilitators can be grouped under the same seven broad categories–patient, health system, medication, stigma, poor mental health, socio-economic and socio-cultural-related factors ( Table 4 ).…”
Section: Resultsmentioning
confidence: 99%